Study of remobilization phenomena at reclaimed asphalt binder/virgin binder interphases for recycled asphalt mixtures using novel microscopic methodologies. (20th March 2018) - Vassaux, S.; Gaudefroy, V.; Boulangé, L.; Soro, L. Jean; Pévère, A.; Michelet, A.; Barragan-Montero, V.; Mouillet, V.
Graphical abstract: Highlights: Infrared Imaging ATR is a suitable technique to investigate binder remobilization. Carbonyl distribution profile is efficient to monitor the aged binder migration. The aged binder viscosity influences significantly the distribution profile slope. Higher the aged binder temperature, longer the blending length between binders. The rejuvenator addition improves the aged binder remobilization. Abstract: Objectives are to understand remobilization phenomena which occur during the manufacture of recycled asphalt mixtures. Novel X-ray micro fluorescence and infrared microscopy methodologies have been customized to the "aged binder/virgin binder" interphase. Infrared Imaging ATR is the best technique to monitor the aged binder migration coupled to the carbonyl function as a distinguishable marker. Furthermore, the rejuvenator addition and a high aged binder temperature increase the blending zone length between binders. The carbonyl distribution profile slope assesses also the binders blend quality and directly depends on the aged binder viscosity. Another impacting factor could also influence the binder remobilization and could be based on molecular distributions.